The Libyan pharaohs of Egypt : their lives and afterlives - Dodson, Aidan, 1962- (The American University in Cairo Press, 2025)
""During the tenth through seventh centuries BC, Egypt was ruled by a series of pharaohs of Libyan ancestry. The Libyans had hitherto been enemies of the Egyptians, with conflicts going back into the third millennium BC. Yet during the eleventh century we find Libyan names among members of Egyptian elite families, and early in the next century a pharaoh of Libyan descent ascended the Egyptian throne. There is no evidence of any violent take-over, so it appears likely that ongoing immigration and intermarriage with the Egyptian elites had brought a Libyan line to this point. Although the earlier Libyan pharaohs seem to have maintained the tradition of a unitary Egyptian state, as time went by Libyan ideas of decentralised control became more prevalent. As a result, we find individuals holding both Libyan and Egyptian titles controlling distinct territories around Egypt, some of whom assumed the names and titles of a pharaoh. Conflict sometimes accompanied this process, with a long civil war fought for the control of southern Egypt and the great religious capital of Thebes. Some degree of central control was imposed with the advent of a further set of rulers from Nubia during the eight century, but a single Egyptian state would not be restored until the middle of the seventh century. This book reconstructs the story of this era, covering not only its complex political history, but also its monuments - both for the living and the dead - and its aftermath, including the rediscovery of its kings and monuments in modern times.""--